Phonological and Visuospatial Working Memory in Autism Spectrum Disorders. - Macizo, P.; Soriano, M.; Paredes, N. (Journal of Autism & Developmental Disorders, 2016)
We evaluated phonological and visuospatial working memory (WM) in autism spectrum disorders. Autistic children and typically developing children were compared. We used WM tasks that measured phonological and visuospatial WM up to the capacity limit of each children. Overall measures of WM did not show differences between autistic children and control children. However, when the recall of children was examined in detail, autistic children showed reduced phonological WM compared with control children. Moreover, phonological and visuospatial WM did not increase with the age of autistic children while a development of phonological and visuospatial WM with age was found in control children. The pattern of results is discussed in terms of previous studies about WM and autism.